2017
DOI: 10.13040/ijpsr.0975-8232.8(6).2496-03
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pharmacological activities have been reported for the fruit, leaf and root extracts of Morinda citrifolia L. (Noni); however, the plant has not been widely studied for its antidyslipidemic effects on obesity and metabolic syndrome (MS). Objective: to evaluate the effects of aqueous M. citrifolia leaf extract on obesity and adipose tissue cell dynamics associated with triacylglycerol and adiponectin levels in Wistar rats with MS. Methodology: four groups of rats were used; control, metabolic syndrome (MS), M. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The recent focus on the development and use of natural products as a medical option for the treatment of obesity in animal models has demonstrated that M. citrifolia may be an alternative for the treatment of this disease (Inada et al, 2017). Ida et al (2017) verified the effects of the dry leaf extract of M. citrifolia on the dynamics of adipose tissue cells associated with the levels of triacylglycerol and adiponectin in Wistar rats, with consequent evaluation of the levels of obesity in rats suffering from the metabolic syndrome (MS). Among the groups of populations of rats used in this study, differences in abdominal fat weights were observed between the groups treated with noni leaf extract and the control group, without the treatment with the extract.…”
Section: Activity Against Metabolic Disorders Associated With Obesitymentioning
confidence: 99%
“…The recent focus on the development and use of natural products as a medical option for the treatment of obesity in animal models has demonstrated that M. citrifolia may be an alternative for the treatment of this disease (Inada et al, 2017). Ida et al (2017) verified the effects of the dry leaf extract of M. citrifolia on the dynamics of adipose tissue cells associated with the levels of triacylglycerol and adiponectin in Wistar rats, with consequent evaluation of the levels of obesity in rats suffering from the metabolic syndrome (MS). Among the groups of populations of rats used in this study, differences in abdominal fat weights were observed between the groups treated with noni leaf extract and the control group, without the treatment with the extract.…”
Section: Activity Against Metabolic Disorders Associated With Obesitymentioning
confidence: 99%